Employment and Wage Disparities for Nurses With Activity Limitations. Issue 6 (13th October 2016) - Wilson, Barbara L.; Butler, Richard J.; Butler, Matthew J.
Abstract: Purpose: No studies quantify the labor market disparities between nurses with and without activity difficulties (physical impairment or disability). We explore disparate treatment of nurses with activity difficulties at three margins of the labor market: the ability to get a job, the relative wage rate offered once a nurse has a job, and the annual hours of work given that wage rate. Design: Key variables from the American Community Survey (ACS) were analyzed, including basic demographic information, wages, hours of work, and employment status of registered nurses from 2006 to 2014. Findings: Although there is relatively little disparity in hourly wages, there is enormous disparity in the disabled's employment and hours of work opportunities, and hence a moderate amount of disparity in annual wages. Conclusions: This has significant implications for the nursing labor force, particularly as the nursing workforce continues to age and physical limitations or disabilities increase by 15‐fold from 25 to 65 years of age. Clinical Relevance:  Physical or psychological difficulties increase sharply over the course of a nurse's career, and employers must heighten efforts to facilitate an aging workforce and provide appropriate job accommodations for nurses with activity limitations.